Canine Haemophilic Arthropathy: Magnetic Resonance Imaging and Histologic Assessment of Joints in Two Adult Beagles with Confirmed Factor Deficiencies - Pownder, Sarah L.; Caserto, Brian G.; Brooks, Marjory B.; Hayashi, Kei (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
Two adult female Beagle dogs, one case each of hereditary Factor VII deficiency and Factor IX deficiency, were evaluated post-mortem for joint pathology associated with haemophilic arthropathy (HA) using magnetic resonance imaging and histology. Cadaveric magnetic resonance imaging and histologic findings demonstrated severe HA for the Factor IX deficiency dog, with only mild abnormalities for the Factor VII deficiency dog. Signs of HA were similar to humans, including cartilage degeneration, subchondral cysts, peripheral erosions, neovascularization, synovial inflammation and hyperplasia, hemosiderin deposition, haematoma and osteoporosis. Magnetic resonance imaging examination can be used to help identify features of HA in dogs that have experienced repeated joint bleeds.
Keywords: haemophilia; haemarthrosis; canine; MRI; histopathology